THE EFFECTIVENESS OF COMBINED GROUP TASK THERAPY IN MOTOR REHABILITATION FOR PATIENTS WITH ISCHEMIC STROKE AT SON TAY GENERAL HOSPITAL, HA NOI - Phan, Van Minh (Tạp chí Sinh lý học Việt Nam, 2024)
Objective: To evaluate the effectiveness of combined group task therapy in motor rehabilitation for patients with ischemic stroke. Methods: Interventional study, comparing before and after treatment on 32 patients with ischemic stroke treated at Son Tay General Hospital, Ha Noi from May 2024 to October 2024. Rehabilitation intervention includes physical therapy: 20 minutes/day, occupational therapy: 20 minutes/day combined with group task therapy for balance and walking 60 minutes/day, 05 sessions/week, evaluated after 4 weeks of treatment. Results: After 4 weeks of treatment, there was an improvement in balance ability (BBS), Berg score increased by 19 ± 4 points (p<0.001). There was an improvement between the time to stand and walk (TUG) before and after the intervention of 8.51 ± 3.84 seconds (p<0.001). Improvement in walking speed (10MWT) increased by 0.26 ± 0.11 m/s (p<0.01). Improvement in distance traveled in the 2-minute walk test (2MWT) increased to an average of 41.32 ± 0.75 m (p<0.001). Conclusion: Intervention of motor rehabilitation combined with group task therapy in 32 patients with ischemic stroke at Son Tay General Hospital after 4 weeks of intervention, we found an improvement in BBS score, standing up and walking time before, and after TUG intervention. After intervention, patients had improved 10 m walking speed and improved distance traveled in the 2-minute walking test.